2010
DOI: 10.1017/s1462399409001343
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of host APOBEC3 restriction factors with HIV-1 in vivo: implications for therapeutics

Abstract: Restriction factors are natural cellular proteins that defend individual cells from viral infection. These factors include the APOBEC3 family of DNA cytidine deaminases, which restrict the infectivity of HIV-1 by hypermutating viral cDNA and inhibiting reverse transcription and integration. HIV-1 thwarts this restriction activity through its accessory protein virion infectivity factor (Vif), which uses multiple mechanisms to prevent APOBEC3 proteins such as APOBEC3G and APOBEC3F from entering viral particles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
194
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 169 publications
(205 citation statements)
references
References 174 publications
(278 reference statements)
7
194
0
3
Order By: Relevance
“…Several human APOBEC3 (apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3) proteins, notably APOBEC3D, APOBEC3F, APOBEC3G and APOBEC3H, have the capacity to restrict human immunodeficiency virus type 1 (HIV-1) replication (Albin & Harris, 2010;Desimmie et al, 2014;Feng et al, 2014;Kitamura et al, 2011;Refsland & Harris, 2013). These restriction factors are incorporated into the progeny virions and enzymically convert viral cDNA cytosines to uracils during reverse transcription, which can debilitate viral function (Albin & Harris, 2010;Desimmie et al, 2014;Feng et al, 2014;Kitamura et al, 2011;Refsland & Harris, 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several human APOBEC3 (apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3) proteins, notably APOBEC3D, APOBEC3F, APOBEC3G and APOBEC3H, have the capacity to restrict human immunodeficiency virus type 1 (HIV-1) replication (Albin & Harris, 2010;Desimmie et al, 2014;Feng et al, 2014;Kitamura et al, 2011;Refsland & Harris, 2013). These restriction factors are incorporated into the progeny virions and enzymically convert viral cDNA cytosines to uracils during reverse transcription, which can debilitate viral function (Albin & Harris, 2010;Desimmie et al, 2014;Feng et al, 2014;Kitamura et al, 2011;Refsland & Harris, 2013).…”
mentioning
confidence: 99%
“…These restriction factors are incorporated into the progeny virions and enzymically convert viral cDNA cytosines to uracils during reverse transcription, which can debilitate viral function (Albin & Harris, 2010;Desimmie et al, 2014;Feng et al, 2014;Kitamura et al, 2011;Refsland & Harris, 2013). Although original studies focused on human APOBEC3G (Harris et al, 2003;Mariani et al, 2003;Sheehy et al, 2002;Zhang et al, 2003), subsequent work revealed that all placental mammals have APOBEC3 enzymes (Münk et al, 2012), albeit different numbers, and that these enzymes have the potential to attenuate the infectivity of a broad spectrum of viruses, including simian immunodeficiency virus (SIV) (Mariani et al, 2003), feline immunodeficiency virus (FIV) (Münk et al, 2008;Zielonka et al, 2010), bovine immunodeficiency virus (BIV) (LaRue et al, 2010) and small ruminant lentiviruses (SRLVs; e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The apolipoprotein B mRNA-editing, enzyme-catalytic, polypeptide-like 3 family (APOBEC3) proteins comprise six members of cytidine deaminases (6). The expression of APOBEC3G (A3G) is elevated in monocyte-derived DCs (MDDCs) upon maturation, leading to suppression of reverse transcription and introduction of G-to-A hypermutations in the viral genome.…”
mentioning
confidence: 99%
“…The expression of APOBEC3G (A3G) is elevated in monocyte-derived DCs (MDDCs) upon maturation, leading to suppression of reverse transcription and introduction of G-to-A hypermutations in the viral genome. Two other members of the A3 family, A3F and A3A, were also shown to be expressed in MDDCs and exert antiviral activity (6)(7)(8). Although humans have evolved powerful retroviral restriction factors, HIV-1 has acquired specific means to antagonize these antiviral defense mechanisms.…”
mentioning
confidence: 99%